Multiple year influences of the aflatoxin biocontrol product AF-X1 on the A. flavus communities associated with maize production in Italy - Ouadhene, M.A.; Ortega-Beltran, A.; Sanna, M.; Cotty, P.J.; Battilani, P. (MDPI, 2023)
AF-X1 is a commercial aflatoxin biocontrol product containing the non-aflatoxigenic (AF-) strain of Aspergillus flavus MUCL54911 (VCG IT006), endemic to Italy, as an active ingredient. The present study aimed to evaluate the long-term persistence of VCG IT006 in the treated fields, and the multi-year influence of the biocontrol application on the A. flavus population. Soil samples were collected in 2020 and 2021 from 28 fields located in four provinces in north Italy. A vegetative compatibility analysis was conducted to monitor the occurrence of VCG IT006 on the total of the 399 isolates of A. flavus that were collected. IT006 was present in all the fields, mainly in the fields treated for 1 yr or 2 consecutive yrs (58% and 63%, respectively). The densities of the toxigenic isolates, detected using the aflR gene, were 45% vs. 22% in the untreated and treated fields, respectively. After displacement via the AF- deployment, a variability from 7% to 32% was noticed in the toxigenic isolates. The current findings support the long-term durability of the biocontrol application benefits without deleterious effects on each fungal population. Nevertheless, based on the current results, as well as on previous studies, the yearly applications of AF-X1 to Italian commercial maize fields should continue.